1986
DOI: 10.1021/bi00368a019
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation and inactivation in the presence of antithrombin III and heparin

Abstract: We have determined the rate constants of inactivation of factor Xa and thrombin by antithrombin III/heparin during the process of prothrombin activation. The second-order rate constant of inhibition of factor Xa alone by antithrombin III as determined by using the synthetic peptide substrate S-2337 was found to be 1.1 X 10(6) M-1 min-1. Factor Xa in prothrombin activation mixtures that contained prothrombin, and either saturating amounts of factor Va or phospholipid (20 mol % dioleoylphosphatidylserine/80 mol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 21 publications
5
33
0
Order By: Relevance
“…As a result, the generation of factor Xa will be reduced hence producing a pattern of factor X deficiency. On the other hand, the initial product of factor II conversion, meizothrombin, is not inhibited by antithrombin/ heparin [14,25], so that factor VIII will still be activated, and an inhibition of subse quently formed factor Ila will only be a sec ondary event.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the generation of factor Xa will be reduced hence producing a pattern of factor X deficiency. On the other hand, the initial product of factor II conversion, meizothrombin, is not inhibited by antithrombin/ heparin [14,25], so that factor VIII will still be activated, and an inhibition of subse quently formed factor Ila will only be a sec ondary event.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, not only does locally formed thrombin become inactivated by FPRCH2C1, but the resultant inactive complex, FPRCH2-thrombin, occupies the platelet thrombin receptors of ambient platelets to prevent subsequent activation by thrombin. Second, FPRCH2C1 may inactivate platelet-bound meizothrombin (33) during thrombin generation. Since thrombin formation is generally a process associated with the cell surface, particularly the platelet membrane, covalent inactivation by FPRCH2C1 may occur after the activating cleavage but before thrombin is freed from the platelet-bound fragment 1.2.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin is well known to form a complex with plasma antithrombin III, and then this complex neutralizes thrombin. Argatroban, on the other hand, binds directly to the active sites of the thrombin molecule (23). Hanson and Harker (24) have shown that argatroban, which is a relatively small molecule, can diffuse into the thrombus and interact with thrombin that is bound to platelet receptors.…”
Section: Discussionmentioning
confidence: 99%